Estimation of Potential Domestic Investor Demand for the Issuance of Government Islamic Securities (SBSN) Project Based Participation Fund (Sukuk) and Benefits for Issuers and Investors - Wulan Indriani (STIE Binaniaga, 2022)
SBSN PBS is one of Islamic securities issued by the government since 2012. It has a special purpose to finance the infrastructure development in Indonesia. Due to the incremental of Islamic finance industry, it has affected the increasing of the demand for SBSN PBS each year. Therefore, this research intends to determine the potential demand of them, how to fulfil such a demand and the benefits for both the issuer and the investors.The thesis uses qualitative and quantitative approaches to determine the market’s view, analyze the prognosis of its supply and demand with least square method, and the benefits that will be obtained from the issuance of SBSN PBS. The results of the study indicate that the growth of SBSN PBS issuance is estimated has a positive trend with CAGR 6.7% over the next 5 years. Besides, its demand has also had a high potential absorption. The growth is estimated to be CAGR 9.6% with a bid to cover ratio 3 times until 4 times higher than its supplies.Therefore, with the good market response, the government needs to consider; (i)the total proceeding value of SBSN PBS issuance, (ii)increasing the frequency of auctions, (iii)and prioritizing SBSN PBS than others.